The Main Factors of Yemeni Conflict: An Analysis - Adeb Abdulelah Abdulwahid Al-Tamimi; Uddagatti Venkatesha (LPPM Universitas Abdurrab, 2021)
Yemen is an unsteady country with a long history of conflict and many complex issues that have led to the deterioration of the political, economic, and social situation. The conflict in its various stages began as an internal political struggle as a result of the people's grievances and the elite's competition for power and national wealth, in addition to other external factors. Hence, it is important to study the conflict factors in Yemen to understand the situation which in turn will help in providing solutions by decision-makers towards peace-making. Therefore, this study analyses the conflict factors in Yemen based on the political, economic, and social effects, in addition to the external interference effects. The research findings indicated that the conflict factors were not the only result of security or political issues but also presented by many socio-economic problems as well as external factors, which have affected of the country since its unification.